Senotherapeutics: targeting senescence in idiopathic pulmonary fibrosis - Merkt, Wolfgang (Seminars in cell & developmental biology, 2020)
Idiopathic pulmonary fibrosis (IPF) is a fatal chronic lung disease characterized by progressive scarring of the lung tissue, leading to respiratory failure. There is no cure for IPF, and current anti-fibrotic treatments modestly arrest its further progression. IPF prevalence and incidence increase with age, which is a recognized risk factor. Intense clinical and basic research over the last fifteen years has shown that hallmarks of accelerated aging are present in the lungs of patients with IPF. Different cell types in IPF lungs exhibit premature hallmarks of aging, including telomere attrition and cellular senescence. In this Review, we discuss recent insights into the mechanisms behind these age-related alterations and their contribution to the development of lung fibrosis. We focus on the genetic and molecular basis of telomere attrition in alveolar type II epithelial cells, which promote cellular senescence and lung fibrosis. Mechanistically, senescent cells secrete pro-fibrotic factors that activate scar-forming myofibroblasts. Ultimately, senescent alveolar epithelial cells lose their regenerative capacity, impeding fibrosis resolution. In addition, mitochondrial dysfunction is strongly associated with the appearance of senescent epithelial cells and senescent myofibroblasts in IPF, which persist in the fibrotic tissue by adapting their metabolic pathways and becoming resistant to apoptosis. We discuss emerging novel therapeutic strategies to treat IPF by targeting cellular senescence with the so-called senotherapeutics.